Identification of candidate genes for key fibre‐related QTLs and derivation of favourable alleles in Gossypium hirsutum recombinant inbred lines with G. barbadense introgressions. Issue 3 (20th September 2019) - Wang, Furong; Zhang, Jingxia; Chen, Yu; Zhang, Chuanyun; Gong, Juwu; Song, Zhangqiang; Zhou, Juan; Wang, Jingjing; Zhao, Chengjie; Jiao, Mengjia; Liu, Aiying; Du, Zhaohai; et al.
Summary: Fine mapping QTLs and identifying candidate genes for cotton fibre‐quality and yield traits would be beneficial to cotton breeding. Here, we constructed a high‐density genetic map by specific‐locus amplified fragment sequencing (SLAF‐seq) to identify QTLs associated with fibre‐quality and yield traits using 239 recombinant inbred lines (RILs), which was developed from LMY22 (a high‐yield Gossypium hirsutum L. cultivar) × LY343 (a superior fibre‐quality germplasm with G . barbadense L. introgressions). The genetic map spanned 3426.57 cM, including 3556 SLAF‐based SNPs and 199 SSR marker loci. A total of 104 QTLs, including 67 QTLs for fibre quality and 37 QTLs for yield traits, were identified with phenotypic data collected from 7 environments. Among these, 66 QTLs were co‐located in 19 QTL clusters on 12 chromosomes, and 24 QTLs were detected in three or more environments and determined to be stable. We also investigated the genomic components of LY343 and their contributions to fibre‐related traits by deep sequencing the whole genome of LY343, and we found that genomic components from G. hirsutum races (which entered LY343 via its G . barbadense parent) contributed more favourable alleles than those from G. barbadense . We further identified six putative candidate genes for stable QTLs, including Gh_A03G1147 ( GhPEL6 ), Gh_D07G1598 ( GhCSLC6 ) and Gh_D13G1921 ( GhTBL5 ) for fibre‐length QTLs and Gh_D03G0919 ( GhCOBL4 ), Gh_D09G1659 ( GhMYB4 ) and Gh_D09G1690 ( GhMYB85 ) for lint‐percentage QTLs. Our results provide comprehensive insight into the genetic basis of the formation of fibre‐related traits and would be helpful for cloning fibre‐development‐related genes as well as for marker‐assisted genetic improvement in cotton.